USE OF TIO2 AS A REINFORCEMENT OF CASSAVA STARCH/PVA COMPOSITES ON MOISTURE-RESISTANT PROPERTIES OF TRIBOELECTRIC NANOGENERATORS (TENG) FILM - Ansori, Aris; Soeparman, Sudjito; Widhiyanuriyawan, Denny; Widodo, Teguh Dwi (IIUM Engineering Journal, 2023)
High humidity environments can accelerate the transmission, neutralization, or dissipation of frictional charges on the frictional surface of solid-solid triboelectric nanogenerator films (TENGs), which can reduce the output power. The moisture resistance properties of the TENG triboelectric film are needed to overcome these problems. Therefore, this study discusses the role of the TiO2 nanofiller in cassava starch (CS) and polyvinyl alcohol (PVA) nanocomposite matrix that can increase triboelectricity through the formation of hydrogen bonds and the provision of oxygen-free electrons. The research method was to incorporate different concentrations of TiO2 nanoparticles (0%, 0.5%, 1%, 5%, 10% wt, and 15% wt) into the CS-PVA nanocomposite matrix using the solvent casting method. The results showed an increase in surface polarity which was more triboelectric-positive due to the CS-PVA hydroxyl group interacting with water molecules. Increasing the concentration above 5% wt TiO2 increases the density of the CS-PVA nanocomposite film which can significantly reduce water vapor permeability (WVP) and increase water resistance. The TENG performance of the CS-PVA/TiO2 nanocomposite film with a concentration of 15% wt TiO2 under conditions of high humidity (RH, 95%) resulted in an output voltage of 2.5-fold (~70.5 V to ~180 V), and the output current increased 2.6-fold (~5.2 ?A to ~13.7 ?A). ABSTRAK: Persekitaran berkelembapan tinggi dapat mempercepatkan penghantaran, peneutralan, atau pelesapan cas geseran pada permukaan geseran filem nanopengeluaran triboelektrik pepejal (TENG), di mana mengurangkan pengeluaran tenaga. Sifat rintangan lembapan filem triboelektrik TENG diperlukan bagi mengatasi masalah ini. Oleh itu, kajian ini membincangkan peranan pengisi nano TiO2 dalam matriks nanokomposit kanji ubi kayu (CS) dan polivinil alkohol (PVA) yang dapat meningkatkan triboelektrik melalui pembentukan ikatan hidrogen dan bekalan elektron bebas oksigen. Kaedah kajian ini adalah dengan menggabungkan kepekatan nanozarah TiO2 berbeza (0%, 0.5%, 1%, 5%, 10%, dan 15%) ke dalam matriks nanokomposit CS-PVA menggunakan kaedah tuangan pelarut. Dapatan kajian menunjukkan peningkatan kekutuban permukaan yang lebih positif-triboelektrik adalah disebabkan oleh kumpulan hidroksil CS-PVA yang berinteraksi dengan molekul air. Pertambahan jisim kepekatan TiO2 melebihi 5% meningkatkan ketumpatan filem nanokomposit CS-PVA yang boleh mengurangkan kebolehtelapan wap air dan meningkatkan rintangan air dengan ketara. Prestasi TENG filem nanokomposit CS-PVA/TiO2 dengan jisim kepekatan TiO2 15% dalam keadaan berkelembapan tinggi (RH, 95%) menghasilkan voltan keluaran sebanyak 2.5 kali ganda (~70,5 V kepada ~ 180 V), dan arus keluaran meningkat 2.6 kali ganda (~ 5,2 ?A kepada ~ 13,7 ?A).